5 years old and stressed out ; Takbo, vendors, takbo! ; Sailing, Pinoy style [videorecording] - Lazaro, Cheche (The Probe Team)
Tackles education in the pre-school; street vendors; and the Parao, a pre-historic fishing vessel and a means for transportation.